Evaluation of Health Care Disparities in Patients With Anterior Cruciate Ligament Injury: Does Race and Insurance Matter?. Issue 9 (29th September 2022) - Farrow, Lutul D.; Scarcella, Michael J.; Wentt, Christa L.; Jones, Morgan H.; Spindler, Kurt P.; Briskin, Isaac; Leo, Brian M.; McCoy, Brett W.; Miniaci, Anthony A.; Parker, Richard D.; Rosneck, James T.; et al.
Background: It is unknown whether race- or insurance-based disparities in health care exist regarding baseline knee pain, knee function, complete meniscal tear, or articular cartilage damage in patients who undergo anterior cruciate ligament reconstruction (ACLR). Hypothesis: Black patients and patients with Medicaid evaluated for ACLR would have worse baseline knee pain, worse knee function, and greater odds of having a complete meniscal tear. Study Design: Cross-sectional study; Level of evidence, 3. Methods: A cohort of patients (N = 1463; 81% White, 14% Black, 5% Other race; median age, 22 years) who underwent ACLR between February 2015 and December 2018 was selected from an institutional database. Patients who underwent concomitant procedures and patients of undisclosed race or self-pay status were excluded. The associations of race with preoperative Knee injury and Osteoarthritis Outcome Score (KOOS) Pain subscale, KOOS Function subscale, and intraoperatively assessed complete meniscal tear (tear that extended through both the superior and the inferior meniscal surfaces) were determined via multivariate modeling with adjustment for age, sex, insurance status, years of education, smoking status, body mass index (BMI), meniscal tear location, and Veterans RAND 12-Item Health Survey Mental Component Score (VR-12 MCS). Results: The 3 factors most strongly associated with worse KOOS Pain and KOOS Function were lower VR-12 MCS score, increased BMI, and increased age. Except for age, the other two factors had an unequal distribution between Black and White patients. Univariate analysis demonstrated equal baseline median KOOS Pain scores (Black, 72.2; White, 72.2) and KOOS Function scores (Black, 68.2; White, 68.2). After adjusting for confounding variables, there was no significant difference between Black and White patients in KOOS Pain, KOOS Function, or complete meniscal tears. Insurance status was not a significant predictor of KOOS Pain, KOOS Function, or complete meniscal tear. Conclusion: There were clinically significant differences between Black and White patients evaluated for ACLR. After accounting for confounding factors, no difference was observed between Black and White patients in knee pain, knee function, or complete meniscal tear. Insurance was not a clinically significant predictor of knee pain, knee function, or complete meniscal tear.